Eliminating the Board of Pharmacy’s Role in Designating a Pharmacist-in-Charge - Adams, Alex J. (Innov Pharm, 2020)
Nearly all states require that each licensed pharmacy designate a pharmacist-in-charge (PIC). By law, the PIC typically has responsibility for all professional practice laws and facility standards laws and can be held accountable for such. However, the extent to which the PIC has actual authority over many facility standards varies by organization. This can seemingly put a target on the back of the PIC for decisions they wield little authority over. Idaho recently removed the legal references to the PIC, signaling that facilities are responsible for facility standards and insulating pharmacists from discipline for matters that are outside their control.